The genus Coeloides Wesmael of subfamily Braconinae (Hymenoptera: Braconidae) in China - Wang, Yi-Ping; Chen, Xue-Xin; Wu, Hong; He, Jun-Hua (Zootaxa, 2006)
The species of Coeloides Wesmael of the tribe Coeloidini (Hymenoptera: Braconidae: Braconinae) are revised in China, and eleven species are recognized. Among them, four new species: C. glaboventris Wang et Chen, sp. nov., C. longquanus Wang et Chen, sp. nov., C. flavus Wang et Chen, sp. nov. and C. changbaiensis Wang et Chen, sp. nov., are described and illustrated in detail. Some of the known species of this genus and one new species, C. flavus Wang et Chen described in this paper are parasitoids of larvae of various species of Scolytidae, Curculionidae and Buprestidae (Coleoptera), many of which are notorious pests in coniferous and broadleaved trees. The type and other voucher specimens are deposited in the Parasitic Hymenoptera Collection, Zhejiang University, Hangzhou, and Chinese Academy of Forestry, Beijing, China.